Multicultural Values in the New Paradigm of Al Islam and Kemuhammadiyahan as an Effort to Prevent Radiacialism in Muhammadiyah Universities - Irfani, Muhammad; Ali Mustofa, Triono (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The rise of an understanding of radicalism, especially in the university environment, indicates that conditions in that environment are not good - fine, the biggest factor in the increasingly widespread understanding of radicalism is because someone is wrong when he understands religion. Muhammadiyah, which is an Islamic organization that is concerned with education, has a step to ensure that students stay on the "track" when they are religious, namely with the learning of Al Islam and Kemuhammadiyahan which has the aim of renewing thinking, completing recreation from a religious point of view, philosophical system, large, strategic, and schooling.This research is classified as qualitative research using the type of library research (library study) with documentation data collection.The purpose of this study is to describe the understanding of radicalism and multicultural values in the new paradigm of Al Islam and Kemuhammadiyahan. The results of this study Radicalism is an understanding that requires the presence of change, substitution, and breaking the social framework to the roots and there are four values of multiculturalism in the new paradigm of AIK, such as: the perspective of theoantopocentrism, understanding the instructions (nash) intelligently, critically and contextually, humans as khalifah and Abdullah and the perspective of zuhud (ascetic) life.